Coencapsulation of Target Effector Cells with Mesenchymal Stem Cells Reduces Pericapsular Fibrosis and Improves Graft Survival in a Xenotransplanted Animal Model. Issue 7 (July 2016) - Vaithilingam, Vijayaganapathy; Evans, Margaret D. M.; Rowe, Anthony; Bean, Penelope A.; Tuch, Bernard E.
Pericapsular fibrotic overgrowth (PFO) is a problem that thwarts full implementation of cellular replacement therapies involving encapsulation in an immunoprotective material, such as for the treatment of diabetes. Mesenchymal stem cells (MSCs) have inherent anti-inflammatory properties. We postulated that coencapsulation of MSCs with the target cells would reduce PFO. A hepatoinsulinoma cell line (HUH7) was used to model human target cells and was coencapsulated with either human or mouse MSCs at different ratios in alginate microcapsules. Viability of encapsulated cells was assessed in vitro and xenografted either intraperitoneally or subcutaneously into C57BL/6 mice. Graft retrieval was performed at 3 weeks posttransplantation and assessed for PFO. Coencapsulation of human MSCs (hMSCs) or mouse MSCs (mMSCs) with HUH7 at different ratios did not alter cell viability in vitro. In vivo data from intraperitoneal infusions showed that PFO for HUH7 cells coencapsulated with hMSCs and mMSCs in a ratio of 1:1 was significantly reduced by 30% and 35%, respectively, compared to HUH7 encapsulated alone. PFO for HUH7 cells was reduced by 51% when the ratio of mMSC/HUH7 was increased to 2:1. Implanting the microcapsules subcutaneously rather than intraperitoneally substantially reduced PFO in all treatment groups, which was most significant in the mMSC/HUH7 2:1 group with a 53% reduction in PFO compared with HUH7 alone. Despite the reduced PFO reaction to the individual microcapsules implanted subcutaneously, all microcapsule treatment groups were contained in a vascularized fibrotic pouch at 3 weeks. The presence of MSCs in microcapsules retrieved from these fibrotic pouches improved graft survival with significantly higher cell viabilities of 83.1 ± 0.6% and 79.1 ± 0.8% seen with microcapsules containing mMSC/HUH7 at 2:1 and 1:1 ratios, respectively, compared to HUH7 alone (51.5 ± 0.7%) transplanted subcutaneously. This study showed that coencapsulation of MSCs with target cells has a dose-dependent effect on reducing PFO and improving graft survival when implanted either intraperitoneally or subcutaneously in a stringent xenotransplantation setting.